Nutrition: The position in English to-day - M'Gonigle, G. C. M. (George Cuthberth Mura), -1939 (London : Industrial Christian Fellowship)
1936-11 1936 1930s 15 pages the hair, the skin, the brain, the muscles, the liver and the kidneys. These varied organs and tissues differ greatly in composition. A bone contains large quantities of mineral salts, but the brain or the skin is built up of quite different materials. If the growing body cannot obtain the right building materials in the right form and quantities the tissues are ill-formed, and are jerry-built, and are unable to function properly and to withstand the wear and tear of life. Leg bones which do not contain the right proportion of lime salts are soft and bend with the weight of the body so that the knock-knees or bow-legs rickets develops. Teeth made of poor materials decay rapidly. Blood which lacks necessary elements, such as iron, is anaemic and the tissues are unable to withstand the infection of disease germs. The right materials are necessary for building the growing body and for keeping it in repair and for providing it with energy. A jerry-built house is one in which there is too much sand in the lime, porous bricks, poor timber, and a shortage of paint to preserve the wood. There are many jerry-built bodies because the materials incorporated in their structure were skimped or of poor quality. There has been not a little difference of opinion as to the incidence of malnutrition in our population. There are many who maintain that its incidence is trifling. Others affirm that it is widespread. If by malnutrition is meant only a bodily state resulting from eating insufficient food, and characterised by progressive loss of weight, then those who state that malnutrition is rare are correct. Malnutrition has a wider meaning than starvation; it means wrong feeding as distinct from total underfeeding. Used in this sense the word signifies deviation from normal bodily 6 15X/2/217/2